Gambaran Rekam Medis Elektronik terhadap Sistem Informasi Manajemen di RSUD Dr. H. Moch. Ansari Saleh Banjarmasi Tahun 2025 - Rabiatul Adawiah; A. Rasyid Ridha R. (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
Electronic Medical Record (EMR) is a digital documentation system that stores comprehensive information regarding patient identity, examinations, treatments, and medical procedures during care in both inpatient and outpatient settings. The implementation of EMR is a complex process that requires careful management of technology and information systems. Given its critical function in modern healthcare, this study aims to analyze the contribution of EMR to the Management Information System (MIS) at RSUD Dr. H. Moch. Ansari Saleh Banjarmasin. Using a qualitative descriptive approach, the research explores actual conditions, phenomena, and variables related to EMR utilization. The findings show that EMR has been effectively applied and provides substantial benefits in several dimensions. In terms of Content, EMR supports the systematic and complete recording of patients’ social and medical data. In terms of Accuracy, it ensures that information is properly stored, easily traceable, and helps maintain previous medical histories, thereby enhancing diagnostic precision. Regarding Format, EMR follows standard medical record guidelines for health services. In terms of Ease, it simplifies access to data and medical histories, improving efficiency and saving time. Overall, the MIS at RSUD Dr. H. Moch. Ansari Saleh Banjarmasin facilitates computerized health records that enhance data completeness and reliability. The EMR’s main contributions are reflected in three managerial functions—Planning, Control, and Decision Making—which strengthen hospital management performance and service quality.